2019
DOI: 10.1093/sleep/zsz250
|View full text |Cite
|
Sign up to set email alerts
|

Bi-directional relations between stress and self-reported and actigraphy-assessed sleep: a daily intensive longitudinal study

Abstract: Study Objectives Stress is associated with poor and short sleep, but the temporal order of these variables remains unclear. This study examined the temporal and bi-directional associations between stress and sleep and explored the moderating role of baseline sleep complaints, using daily, intensive longitudinal designs. Methods Participants were 326 young adults (Mage = 23.24 ± 5.46), providing >2,500 nights of sleep a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
61
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 56 publications
11
61
2
Order By: Relevance
“…In addition to symptoms of stress predicting poor sleep, we also acknowledge that the reverse pathway is equally plausible; specifically, that poor sleep at night may predict symptoms of stress the next day. In line with this reasoning, a number of previous studies have shown poor sleep to predict daily stress (e.g., Hisler et al, 2019;Yap et al, 2019), presumably because sleep disturbance lowers an individual's capacity to cope with daily stressors, which in turn may perhaps interfere with their responsiveness to opportunities for need satisfaction and exacerbate need frustration throughout the day. Thus, in addition to fatigue, it is equally plausible that symptoms of stress may also play an intervening role in the association between adolescents' sleep at night and their need-based experiences throughout the following day.…”
Section: The Role Of Stressmentioning
confidence: 85%
“…In addition to symptoms of stress predicting poor sleep, we also acknowledge that the reverse pathway is equally plausible; specifically, that poor sleep at night may predict symptoms of stress the next day. In line with this reasoning, a number of previous studies have shown poor sleep to predict daily stress (e.g., Hisler et al, 2019;Yap et al, 2019), presumably because sleep disturbance lowers an individual's capacity to cope with daily stressors, which in turn may perhaps interfere with their responsiveness to opportunities for need satisfaction and exacerbate need frustration throughout the day. Thus, in addition to fatigue, it is equally plausible that symptoms of stress may also play an intervening role in the association between adolescents' sleep at night and their need-based experiences throughout the following day.…”
Section: The Role Of Stressmentioning
confidence: 85%
“…In studies of undergraduate students, those who reported poorer sleep quality or reduced sleep quantity also endorsed elevated rates of depression and/or anxiety [10,13], and those who met criteria for insomnia reported increased rates of stress, fatigue, mental health, hypnotic and stimulant use, and decreased quality of life [12]. A recent longitudinal study found that chronic stress, as well as symptoms of depression, were predictive of sleep onset insomnia and hypersomnia among second-year college students [14], another longitudinal study of college students found that stress and sleep problems were bidirectional [15], and multiple studies have demonstrated that mood disorder diagnoses are often preceded by and predicted by poor sleep [16,17]. The association between stress, disrupted sleep and mental health deserves further research attention in college populations.…”
Section: The Role Of Sleep In Maintaining Mental Healthmentioning
confidence: 99%
“…Third, mediation models were tested with data collected at one point in time, therefore directionality cannot be determined. Evidence from a longitudinal study suggests that stress and poor sleep quality have a complex bidirectional relationship [15]. Findings of another longitudinal study found that insomnia may be a premorbid risk for incident depression, or self-report of depression [17].…”
Section: Study Limitationsmentioning
confidence: 99%
“…Sleep apnea is associated with the activation of the HPA axis and higher cortisol levels compared to persons without a sleep disorder [81]. Reductions in sleep time have been shown to be associated with higher reported stress levels the next day [82]. Conversely, chronic stress has been associated with reduced time spent in REM sleep [83,84].…”
Section: Stress and Periodontitis: The Sleep Connectionmentioning
confidence: 99%